Reproductive biology of female Antarctic spiny plunderfish Harpagifer spinosus (Notothenioidei: Harpagiferidae), from Îles Crozet - Van Der Molen, Silvina; Matallanas, Jesús (Antarctic Science)
On the basis of histological examination, we present the first description of oogenesis in H. spinosus. Eight stages of oocyte development were identified using morphological and histochemical criteria. The development of the oocytes is synchronous, and two clutches grow simultaneously in the ovary. Spawning takes place during the end of summer and the beginning of autumn. Absolute fecundity is low, ranging from 787 to 1504 oocytes. The low fecundity is probably related to parental behaviour. Our data indicate that the features of the reproductive biology of H. spinosus, in spite of its unusual environment, are similar to those observed in other teleost fish. Fil: Van Der Molen, Silvina. Universitat Autònoma de Barcelona; España. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico; Argentina Fil: Matallanas, Jesús. Universitat Autònoma de Barcelona; España